Biokonsentrasi Faktor Logam Berat Pb, Cd, Cr dan Cu pada Ikan Nila (Oreochromis niloticus Linn.) di Karamba Danau Rawa Pening - Hidayah, Anny Miftakhul; Purwanto, Purwanto; Soeprobowati, Tri Retnaningsih (Bioma : Berkala Ilmiah Biologi, 2014)
Lake Rawapening has potential as an aquaculture development especially for caged aquaculture activities. Water quality is one of the important requirements in aquaculture bussiness sustainability and safe fish production for human consumption. Previous researches showed that the cage regions of Lake Rawapening have decreased its water quality in the presence of heavy metal content of Pb, Cd, Cr and Cu in water, sediment and tilapia (Oreochromis niloticus Linn.). This research aimed to determine the value of bio-concentration factors of heavy metals Pb, Cd, Cr and Cu in tilapia (Oreochromis niloticus Linn.) which is cultured in cages Lake Rawapening and maximum daily consumption of tilapia that is safe for human consumption. Sampling was done by purposive random sampling at three cages stations. The results showed that the highest BCF values of heavy metals in tilapia (Oreochromis niloticus Linn.) was on Cu 146-172, while the lowest metal on Cd metal 1.25-2. According to the category of the BCF rate, Cu was categorized as moderately accumulated, whereas Pb, Cd, and Cr were categorized as low accumulated. so that farmed tilapia cages are suitable for consumption. Daily consumption of farmed tilapia in Lake Rawapening was maximum 1,4 kg/day Keywords: Lake Rawapening, heavy metals, tilapia, BCF .